KEBIASAAN MAKAN YANG BERHUBUNGAN DENGAN KESEHATAN REPRODUKSI REMAJA PUTRI DI KABUPATEN BOGOR - Yaktiworo Indriani; Mellova Amir; Iskandar Mirza (Jurnal Gizi dan Pangan, 2009)
This research aims was to study (1) food habits of adolescent girls; (2) the adolescent girls’ efforts in taking care of and obtaining reproductive health; and (3) the relation between food habits, school level, parent’s education level, and social economics level of family towardreproductive health of adolescent girls. This research was a cross-sectional study executed in class level of 1 and 2 of SMA Negeri I and SMP Negeri I of Dramaga District, in Bogor Regency in which 3 classes of each level so that totalize 12 classes.  The number of subject was 169 adolescent girls. The data was collected by interviews and filling up questioners on May through June 2008. The research result showed that food habit between adolescent girls of SMP and SMA was not different and both have not yet meet PUGS, especially still less in number consume of rice, animal products and plain water. Strive in overcoming the sigh appearance nearing and during menstruation which is often done by adolescent girls were by keeping it quiet, body massages, and lay down. Variables of eating frequency together with habitual of eating fruits, animal products, and sour or hot food during menstruation are significantly related with reproductive health of adolescent girls.